2020
DOI: 10.1186/s12903-020-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver diamine fluoride solution application on the bond strength of dentine to adhesives and to glass ionomer cements: a systematic review

Abstract: Background: Silver diamine fluoride (SDF) solution gains increasing popularity in arresting dentine caries in clinical practice. The aim of this systematic review was to summarize the findings from laboratory studies on the influence of SDF application on the bond strength of dentine to various adhesives and to glass ionomer cements (GICs). Methods: Two independent reviewers conducted a literature search in the databases Medline, Ovid, PubMed and Web of Science until 15th August 2019 using the search keywords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 42 publications
4
53
0
5
Order By: Relevance
“…A key and notable limitation of this concept at present is that such high-concentration tagging was found to significantly decrease the bond strengths of dental adhesives to both carious and sound dentin (lowly concentrated stannous chloride has been found to not negatively affect bond strengths) [ 11 ]. Similar findings were reported for treatment of carious dentin using other metal ions, like silver diamine fluoride (SDF) [ 12 ]; for SDF, rinsing off or refreshing the surface mitigated these detrimental effects [ 13 ]. Resolving the issue of decreased bond strengths may allow implementing radiopaque tagging as a standard operative step after selective carious tissue removal and before restoring the cavity [ 10 ].…”
Section: Introductionsupporting
confidence: 63%
“…A key and notable limitation of this concept at present is that such high-concentration tagging was found to significantly decrease the bond strengths of dental adhesives to both carious and sound dentin (lowly concentrated stannous chloride has been found to not negatively affect bond strengths) [ 11 ]. Similar findings were reported for treatment of carious dentin using other metal ions, like silver diamine fluoride (SDF) [ 12 ]; for SDF, rinsing off or refreshing the surface mitigated these detrimental effects [ 13 ]. Resolving the issue of decreased bond strengths may allow implementing radiopaque tagging as a standard operative step after selective carious tissue removal and before restoring the cavity [ 10 ].…”
Section: Introductionsupporting
confidence: 63%
“…This dynamic process involves alternating periods of demineralization and remineralisation of dental hard tissues. The perspective that demineralized dental tissues have potential to be remineralized is increasingly accepted by dental professionals (14) . Therefore, topical application of SDF; is a noninvasive treatment for caries, which has been shown to be effective in arresting dental caries in young children as well as older adults; beside its easy application, low cost and painless procedure.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Yasmi et al (8) (2019) who investigated parental acceptance of SDF, concluded that most parents had concerns about the esthetic impact of SDF. Other adverse effects of SDF treatment were chewing difficulties, food accumulation and difficulty to maintain proper oral hygiene (9). Consequently, two alternative ways has been suggested to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%